Some Characteristics of the Art of the Abkhazian Kingdom (8th–11th centuries) on the Example of the Architectural Decoration - Endoltseva, Ekaterina Yu. (Actual Problems of Theory and History of Art, 2019)
The article deals with the results of the research into the architectural decoration of the Abkhazian Kingdom of the last 10 years. Firstly, the objects which were recently found and identified (fragment of the altar barrier from Dranda church, block with the image of Joseph’s dream, fragment of the carving from Kiach church) are mentioned. Secondly, the objects whose date has been reconsidered (lapidary collection from Anacopia mountain, lapidary collection from Bedia, group of reliefs from Mramba village) are analyzed. Second part of the article is dedicated to the generalization concerning the stylistic groups of reliefs that could be dated to the period of the Abkhazian Kingdom. The first group (slabs from Dranda, from Oligynskoye village, from Anukhva and the block with the image of Joseph’s dream) shows the influence of the best examples of the art of the Byzantine Empire (close to Constantinople’s ateliers) that originates from the Hellenism art. The representations of the second group (slabs with the images of animals from the Anacopia mountain, from the Sukhum mountain, from the Mramba village) are much more primitive interms of style and composition. They have some parallels in the frescoes of the cave churches from Cappadocia.The third group consists of the two fragments of the altar barrier from the so called Voronov church (Tsibilda valley). The scenes that are represented there have some parallels in the art of the Transcaucasi ainfluenced by Persia.